(untitled) - Baumol, William J. (Australia, 2005)
This textbook for an introductory undergraduate audience covers the standard material of microeconomics and presents it as if there is little theoretical controversy in the field. The CD-ROM contains self- testing exercises, graphing workshops, and video lectures (tied to a certain large news network).
Keywords: Microeconomics